p40 immunohistochemistry is an excellent marker in primary lung squamous cell carcinoma - Ahmad Affandi, Khairunisa; Tizen, Nur Maya Sabrina; Mustangin, Muaatamarulain; Md Zain, Reena Rahayu (The Korean Society of Pathologists and the Korean Society for Cytopathology, 2018)
Background Lung cancer is the third most common cancer worldwide. With major advances in the molecular testing of lung cancers and the introduction of targeted therapies, the distinction between adenocarcinoma and squamous cell carcinoma as well as pathologic subtyping has become important. Recent studies showed that p40 is highly specific for squamous and basal cells and is superior to p63 for diagnosing lung squamous cell carcinoma. The aim of this study was to evaluate the use of p40 immunohistochemical stain in the diagnosis of non-small cell lung carcinoma and its potential to replace current p63 antibody as the best immunohistochemical squamous marker. Methods Seventy formalin-fixed paraffin-embedded cases previously diagnosed as primary lung squamous cell carcinoma (n = 35) and lung adenocarcinoma (n = 35) from January 2008 to December 2016 were retrieved. The results of tumour cell immunoreactivity for p40 and p63 antibodies in lung squamous cell carcinoma and lung adenocarcinoma were compared. Results p40 was expressed in 27 cases of lung squamous cell carcinoma (77.1%). All cases of lung adenocarcinoma (35/35, 100%) were negative for p40. p63 expression was positive in 30 cases of lung squamous cell carcinoma (85.7%) and 13 cases of lung adenocarcinoma (37.1%). Reactivity for both p40 and p63 in lung squamous cell carcinoma was strong and diffuse, whereas variable reactivity was observed in lung adenocarcinoma. Conclusions p40 is an excellent marker for distinguishing lung squamous cell carcinoma from adenocarcinoma, and p40 expression is equivalent to p63 expression in lung squamous cell carcinoma.